2022
DOI: 10.3390/plants11131734
|View full text |Cite
|
Sign up to set email alerts
|

High Pollination Deficit and Strong Dependence on Honeybees in Pollination of Korla Fragrant Pear, Pyrus sinkiangensis

Abstract: Pollination deficits can compromise fruit yield and quality and have been reported in several fruit crops. It is unknown whether there is a pollination deficit in the production of Korla fragrant pear, Pyrus sinkiangensis, in China, and if so, whether this deficit can be mitigated by the use of managed honeybees (Apis mellifera). We assessed insect communities, flower visitation, pollination deficit and honeybee contribution to pear pollination in Korla fragrant pear orchards in Xinjiang, China. Insect communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 44 publications
(51 reference statements)
0
6
0
Order By: Relevance
“…NGP also resulted in higher honeybee abundance in mixed pear-apricot orchards. As insect pollination is a limiting factor in Korla fragrant pear (Li et al, 2022), these findings suggest that NGP has a potential to improve crop pollination by honeybees in this crop.…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…NGP also resulted in higher honeybee abundance in mixed pear-apricot orchards. As insect pollination is a limiting factor in Korla fragrant pear (Li et al, 2022), these findings suggest that NGP has a potential to improve crop pollination by honeybees in this crop.…”
Section: Discussionmentioning
confidence: 84%
“…However, our results show that honeybee abundance in pan traps was strongly correlated with pear flower visitation rate, indicating that honeybee abundance in pan traps is a useful indicator for pear flower visitation. Furthermore, in a 2‐year study we showed that honeybee visitation rates were positively associated with initial fruit set and sugar content, but not fruit weight (Li et al, 2022). In addition, the effectiveness of NGP on fruit set and quality has also been reported in Guava and kiwifruit in India (Anita et al, 2012; Jailyang et al, 2022).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations